PENGARUH PENGELUARAN PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI KABUPATEN KETAPANG - B61110042, MARYANTO (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT This study was conducted to analyze the effect of government spending on economic growth in Ketapang during the period 2007 - 2011. The method used was qualitative and quantitative research methods. In qualitative analysis is based on descriptive analysis model aimed to describe the development of each group sector development expenditures and routine expenses undertaken by the Government of Ketapang. While quantitatively to analyze the influence of local government spending on economic growth sector groups (GDP). Â The results of this study indicate that the influence of local government development expenditure groups primary sector, trade and transport, education and culture, apparatus and control positive effect on economic growth. Government spending primary sector groups, trade and transport, education and culture, health and social welfare effect in reducing income inequality among the population, while the economic growth exacerbates income inequality among the population. The local government development expenditure in Ketapang positive and significant effect on economic growth and income distribution. However, not all sectors of development expenditure groups can influence economic growth and equitable distribution of income, the local government in the allocation of development funds in order to more effectively and efficiently by formulating appropriate policies in order to build the infrastructure to support the local economy. Â Keywords: Development Expenditure, Routine expenditure and Economic Growth.